Co‐evaporation process study of Cu2ZnSnSe4 thin films by in situ light scattering and in situ X‐ray diffraction. Issue 2 (21st October 2014) - Hartnauer, Stefan; Wägele, Leonard A.; Syrowatka, Frank; Kaune, Gunar; Scheer, Roland
<x xml:space="preserve">Abstract</x> Multi‐stage co‐evaporation processes for the growth of Cu2ZnSnSe4 (CZTSe) thin films are investigated with time‐resolved in situ angle‐dispersive X‐ray diffraction (in situ XRD). Different preparation protocols were applied and controlled by in situ laser light scattering (in situ LLS). The composition of the deposited layers was adjusted by making use of a stoichiometric transitions in the LLS signal at the point where the Cu content equals the [Zn + Sn]. The ability of in situ XRD to distinguish between CZTSe and ZnSe is used to develop new processes that minimize the formation of ZnSe as a secondary phase. At high temperatures, an initially grown ZnSe layer forms at the Mo interface, which may not be incorporated into the CZTSe due to Zn‐rich preparation conditions. By using lower temperatures at the beginning, CZTSe growth starts directly and a heating step restores the high temperature of the substrate. Thus, the formation of secondary phases is diminished without losing the benefits of higher preparation temperature. The ZnSe growth is reduced and the formation of a continuous layer is not observed.